Effect of vibro-milling time on phase formation and particle size of lead titanate nanopowders - R. Wongmaneerung (2018)
A perovskite-like phase of lead titanate, PbTiO3, nanopowder was synthesized by a solid-state reaction via a rapid vibro-milling technique. The effect of milling time on the phase formation and particle size of PbTiO3powder was investigated. Powder samples were characterized using TG-DTA, XRD, SEM and laser diffraction techniques. It was found that an average particle size of 17 nm was achieved at 25 h of vibro-milling after which a higher degree of particle agglomeration was observed on continuation of milling to 35 h. In addition, by employing an appropriate choice of the milling time, a narrow particle size distribution curve was also observed. © 2005 Elsevier B.V. All rights reserved.